A contingency management method for 30-days abstinence in non-treatment seeking young adult cannabis users - Schuster, Randi Melissa; Hanly, Ailish; Gilman, Jodi; Budney, Alan; Vandrey, Ryan; Evins, A. Eden (Drug and alcohol dependence, 2016)
•Contingency management may be useful for studying the effects of cannabis in youth.•Nearly 90% of the sample attained biochemically confirmed 30-day abstinence.•Abstinence was associated with reduction in concentrations of cannabis metabolites. Rates of young adult cannabis use are rising, perceived harm is at its historical nadir, and most users do not want to quit. Most studies evaluating effects of cannabis use in young adults are cross-sectional, limiting causal inference. A method to reliably induce abstinence periods in cannabis users would allow assessment of the effects of abstinence and resumption of use on a variety of outcomes in a within-subjects, repeated measures design. We examined the efficacy and feasibility of a voucher-based contingency management procedure for incentivizing one month of continuous cannabis abstinence among young adults who reported at least weekly cannabis use, volunteered to participate in a laboratory study, and did not express a desire to discontinue cannabis use long-term. Continuous cannabis abstinence was reinforced with an escalating incentive schedule, and self-report of abstinence was confirmed by frequent quantitative assays of urine cannabis metabolite (THCCOOH) concentration. New cannabis use during the abstinence period was determined using an established algorithm of change in creatinine-adjusted cannabis metabolite concentrations between study visits. Thirty-eight young adults, aged 18–25 years, enrolled and 34 (89.5%) attained biochemically confirmed 30-day abstinence. Among those who attained abstinence, 93.9% resumed regular use within two-weeks of incentive discontinuation. Findings support the feasibility and efficacy of contingency management to elicit short-term, continuous cannabis abstinence among young adult, non-treatment seeking, regular cannabis users. Further work should test the effectiveness of this contingency management procedure for cannabis abstinence in periods longer than one month, which may be required to evaluate some effects of abstinence.